Association between dietary protein intake, diet quality and diversity, and obesity among women of reproductive age in Kersa, Ethiopia - Roba, Aklilu Abrham; Assefa, Nega; Roba, Kedir Teji; Dessie, Yadeta; Hamler, Elena; Fawzi, Wafaie (Frontiers in Public Health, 2023)
In Ethiopia, there is limited evidence on the effect of dietary protein intake on women's body mass index. Therefore, this study investigated the association between dietary protein intake, diet quality, and overweight and obesity. A cross-sectional study was conducted among 897 women of reproductive age. Food frequency questionnaires were used to assess 7-day dietary intake. It was converted into protein and other macro-nutrient intakes, Minimum Dietary Diversity for Women, and Global Dietary Quality Score. Body Mass Index (BMI) of overweight & obese women were defined as ≥ 25 kg/m2. An adjusted odds ratio with a 95% confidence interval (in a multivariate logistic regression model) was used to determine the strength of the association between BMI and dietary protein intake, adjusting for potential confounders. The median dietary protein intake was 41.3 (32.9, 52.6) grams/day or 0.8 (0.6, 1.0) grams/kilogram of body weight/day. The prevalence of overweight and obesity was 7.5% (n=67). Only 220 (24.5%) women could meet the recommended minimum dietary diversity of five or more food groups out of ten per day. Furthermore, only 255 (28.4%) women were found to have a low risk for nutrient adequacy. Interestingly, women who consumed moderate dietary protein had a significantly lower likelihood of being overweight or obese, with AOR of 0.21 (95% CI 0.10-0.48). Similarly, those who consumed a high amount of protein had even lower odds, with AOR of 0.03 (95% CI 0.01-0.14), compared to those who consumed a low amount of dietary protein. Age of 40-49 years (AOR=3.33, 95% CI 1.24-8.95) compared to 18-29 years, non-farmers (AOR=3.21, 95% CI 1.55-6.62), higher consumption of food from unhealthy groups (AOR=1.30, 95% CI 1.05-1.61), and high fat intake (AOR=1.06, 95% CI 1.04-1.09) were associated with overweight and obesity. The study indicated an inverse relationship between BMI and dietary protein intake. It also revealed that women who consumed foods from unhealthy or unhealthy when consumed in excessive amounts were more likely to be overweight or obese. Increasing dietary protein consumption can help reproductive-age women reduce the odds of obesity and overweight. Furthermore, community-based educational programs, policy changes, and healthcare services can support this effort.